The Effects of Screen Time on Early Childhood Development: A Systematic Literature Review - Riama Claudia Christine Lumban Gaol; Nur Alam Fajar (JURNAL INFO KESEHATAN, 2025)
The effects of screen time on young children warrant greater attention, particularly as screen use has increased during the COVID-19 pandemic. Excessive screen exposure in early childhood reduces opportunities for adequate stimulation and limits children’s engagement with their physical and social environments. When children do not receive sufficient developmental stimulation during this critical period, optimal brain development may be affected, potentially leading to delays or disorders across various developmental domains. This review aimed to further examine the negative impact of screen time on early childhood development. Guided by the PRISMA guidelines, a comprehensive search was conducted across Google Scholar, PubMed, and Scopus using the keywords “screen time” and “child development” for articles published between 2021 and 2025. A total of 15 studies met the eligibility criteria. The findings consistently show that excessive screen time negatively affects several aspects of early childhood development, including motor, speech-language, cognitive, and social-emotional domains. The review also underscores the critical role of parents in regulating children’s screen use to mitigate these risks. In conclusion, excessive screen media exposure diminishes developmental stimulation and increases the likelihood of developmental delays; therefore, active parental involvement in managing screen time is essential to promote healthy child development.